1989
DOI: 10.1042/bj2590069
|View full text |Cite
|
Sign up to set email alerts
|

Membrane peptidases in the pig choroid plexus and on other cell surfaces in contact with the cerebrospinal fluid

Abstract: A comprehensive survey of 11 peptidases, all of which are markers for renal microvillar membranes, has been made in membrane fractions prepared from pig choroid plexus. Two fractionation schemes were explored, both depending on a MgCl2-precipitation step, the preferred one having advantages in speed and yield of the activities. The specific activities of the peptidases in the choroid-plexus membranes were, with the exception of carboxypeptidase M, lower than in renal microvillar membranes: those of aminopeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…Additionally, endopeptidase-24.11, which is inhibited by phosphoramidon, is indicated to play a key role in regulating the concentrations of neuropeptides, including enkephalins, in cerebrospinal fluid (18). Three reports (1,17,18) suggest that the hydrolysis of LE administered i.t.v. is largely prevented in the presence of the three PIs: amastatin, captopril, and phosphoramidon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, endopeptidase-24.11, which is inhibited by phosphoramidon, is indicated to play a key role in regulating the concentrations of neuropeptides, including enkephalins, in cerebrospinal fluid (18). Three reports (1,17,18) suggest that the hydrolysis of LE administered i.t.v. is largely prevented in the presence of the three PIs: amastatin, captopril, and phosphoramidon.…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight opioid peptides such as ME and dyn (1-7) are shown to be hydrolyzed in cerebrospinal fluid mainly by aminopeptidase M that is inhibited by amastatin, and the other peptidase activities are suggested to be low in cerebrospinal fluid (17). Additionally, endopeptidase-24.11, which is inhibited by phosphoramidon, is indicated to play a key role in regulating the concentrations of neuropeptides, including enkephalins, in cerebrospinal fluid (18). Three reports (1,17,18) suggest that the hydrolysis of LE administered i.t.v.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, endopeptidase-24.11, which is inhibited by phosphoramidon, is indicated to play a key role in regulating the concentrations of neuropeptides, including enkephalins, in cerebrospinal fluid (11). Three reports (1,10,11) suggested that the hydrolysis of ME-RF administered intra-thirdventricularly is largely prevented in the presence of the three PIs: amastatin, captopril, and phosphoramidon. Therefore, the antinociceptive potency of ME-RF shown in the present study probably largely reflects the real potency of ME-RF itself.…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight opioid peptides such as [Met 5 ]enkephalin (ME) and dynorphin A (1-7) are shown to be hydrolyzed in cerebrospinal fluid mainly by aminopeptidase M that is inhibited by amastatin, and the other peptidase activities are suggested to be low in cerebrospinal fluid (10). Additionally, endopeptidase-24.11, which is inhibited by phosphoramidon, is indicated to play a key role in regulating the concentrations of neuropeptides, including enkephalins, in cerebrospinal fluid (11). Three reports (1,10,11) suggested that the hydrolysis of ME-RF administered intra-thirdventricularly is largely prevented in the presence of the three PIs: amastatin, captopril, and phosphoramidon.…”
Section: Discussionmentioning
confidence: 99%
“…Amastatin and enkephalin analogues were from Sigma Chemical Co (St. Louis, Mo., USA). All other pepti dase assay materials and inhibitors were obtained as noted by Bourne et al [26] and Hooper and Turner [27], The reagents used for immunohistochemistry were obtained as described previously [28], Materials for cell culture were purchased from sources described by Lyall et al [23] and Vaughan and Ball [29]. D384 cells were obtained as described pre viously [23,24] and SH-SY5Y cells [25] were generously provided by Dr J.L.…”
Section: Methodsmentioning
confidence: 99%